2017
DOI: 10.1159/000455833
|View full text |Cite
|
Sign up to set email alerts
|

The rs1277306 Variant of the <b><i>REST</i></b> Gene Confers Susceptibility to Cognitive Aging in an Elderly Taiwanese Population

Abstract: Background/Aims: There is growing evidence that the RE1-silencing transcription factor (REST) gene may contribute to cognitive aging and Alzheimer diseases. In this replication study, we reassessed whether single nucleotide polymorphisms (SNPs) within the REST gene are linked with cognitive aging independently and/or through complex interactions in an older Taiwanese population. Methods: A total of 634 Taiwanese subjects aged over 60 years from the Taiwan Biobank were analyzed. Mini-Mental State Examination (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…This study incorporated subjects from the Taiwan Biobank [4749]. The study cohort consisted of 634 participants.…”
Section: Methodsmentioning
confidence: 99%
“…This study incorporated subjects from the Taiwan Biobank [4749]. The study cohort consisted of 634 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Although in the present review we showed some research reports to depict the related artificial intelligence and machine learning algorithms in the neurobiology of psychiatric disorders, it might be noted that precision psychiatry studies may be further improved by integrating the state-of-the-art artificial intelligence and machine learning frameworks with multi-omics and neuroimaging datasets [17]. Numerous current biobanks have been built to collect multi-omics data, such as the Taiwan Biobank [50][51][52][53][54][55][56][57], the COMBINE Biobank [58], LifeGene [59], and the Korea Healthy Twin Study [60].…”
Section: Limitationsmentioning
confidence: 86%
“…A growing body of evidence suggests that REST may be involved with AD and cognitive aging ( 62 ). A recent replication study has assessed whether REST SNPs are associated with cognitive aging as well as via SNP–SNP interactions for normal aging in elder Taiwanese subjects ( n = 634; mean age: 64.2 years) ( 62 ). Their analysis results demonstrated that REST -rs1277306 was linked with cognitive aging, which was measured by MMSE scores ( 62 ).…”
Section: Recent Association Studiesmentioning
confidence: 99%
“…A recent replication study has assessed whether REST SNPs are associated with cognitive aging as well as via SNP–SNP interactions for normal aging in elder Taiwanese subjects ( n = 634; mean age: 64.2 years) ( 62 ). Their analysis results demonstrated that REST -rs1277306 was linked with cognitive aging, which was measured by MMSE scores ( 62 ). This prediction is further supported by evidence that the association remained significant for individuals without APOE ε4 allele after Bonferroni correction ( 62 ).…”
Section: Recent Association Studiesmentioning
confidence: 99%
See 1 more Smart Citation